Qalandar-name. Chapter 8: “Praises to Four Imams” » - M.R. Shamsimukhametova; D.A. Shagaviev; M.M. Yakubovich (Золотоордынское обозрение)
Presented fragment is the next part of the translation of the medieval poetic text “Qalandar-name” written by Abu Bakr Qalandar, the Sufi scholar from Crimea. This Chapter is devoted to praises to four founders of schools of islamic law (madhhab): an-Numan Abu Hanifa, Mukhammad ash-Shafii, Ahmad ibn Hanbal and Malik ibn Anas. Incorrect order of praises of Imams (Ibn Malik is mentioned after other three imams) shows that author of source belongs to Shafii madhhab. The author mentions the virtues of these imams, making the main emphasis on their knowledge. Reviewing their accomplishments author mentions “hundred usul”, “Mystery of Mohammads soul”, relating to Abu Hanifa. Imam Ibn Hanbal was notable for metapharistic translation of Quran and was called “Imam of faithfuls”(although he was a subject of inquisition by mutazilits for his views on creation of Quran). Malik Ibn Anas “cleaned the house from war and demons”, he was “mujtaheed”; here we give our own rendering of Abu Bakr Qalandar’s assumptions. In this chapter Abu Hanifa is resembled to “mind”, ash-Shafi to “soul”, Ibn Hanbal to “key to perception”, and imam Malik to “revelation” and transition from worldly to spiritual – paring the skin, that was written by many other sufi theorists. Also Abu Bakr acknowledges the legitimacy of this four ‘mazhabs’, writing that ‘all of us should follow this four imams and their students’, meaning branches (furu’), legal thesis of madhhabs, that were introduced later by their students.